Konsep Rahmatan Lil 'Alamin di IAI AL-AZIS Dalam Perspektif Hukum Konstitusi Indonesia - Mutimah Nursabilah Isu; Fathan Al-widad; Toto Jumanta; Ahmad Shofi; Ali Marzuki (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The concept of "Rahmatan lil 'Alamin" in Islam signifies mercy for all creation, as stated in the Qur'an Surah Al-Anbiya' verse 107. This study aims to analyze its implementation at the Institut Agama Islam Al-Zaytun Indonesia (IAI AL-AZIS) through da'wah and educational approaches, as well as its relevance to Indonesian constitutional law. The method employed is library research with qualitative content analysis, drawing data from primary sources (Qur'an, hadith, IAI AL-AZIS documents) and secondary literature (journals and books on Islamic law in Indonesia). Findings reveal that IAI AL-AZIS implements this concept via its institutional anthem and radio streaming da'wah, emphasizing noble character, tolerance, and social harmony. The concept aligns with Pancasila and Article 29 of the 1945 Constitution on religious freedom, representing substantive integration of Islamic values within Indonesia's plural unitary state framework, albeit limited to prevent exceeding constitutional principles that safeguard national unity. The study concludes that the application of rahmatan lil 'alamin at IAI AL-AZIS strengthens tolerance grounded in Islamic values consistent with Indonesia's constitution.